A new tool for tuberculosis vaccine screening: Ex vivo Mycobacterial Growth Inhibition Assay indicates BCG-mediated protection in a murine model of tuberculosis. Issue 1 (December 2016) - Zelmer, Andrea; Tanner, Rachel; Stylianou, Elena; Damelang, Timon; Morris, Sheldon; Izzo, Angelo; Williams, Ann; Sharpe, Sally; Pepponi, Ilaria; Walker, Barry; Hokey, David; McShane, Helen; et al.
Abstract Background In the absence of a validated animal model and/or an immune correlate which predict vaccine-mediated protection, large-scale clinical trials are currently the only option to prove efficacy of new tuberculosis candidate vaccines. Tools to facilitate testing of new tuberculosis (TB) vaccines are therefore urgently needed. Methods We present here an optimizedex vivo mycobacterial growth inhibition assay (MGIA) using a murineMycobacterium tuberculosis infection model. This assay assesses the combined ability of host immune cells to inhibit mycobacterial growth in response to vaccination. C57BL/6 mice were immunized with Bacillus Calmette-Guérin (BCG) and growth inhibition of mycobacteria by splenocytes was assessed. Mice were also challenged withMycobacterium tuberculosis Erdman, and bacterial burden was assessed in lungs and spleen. Results Using the growth inhibition assay, we find a reduction in BCG CFU of 0.3–0.8 log10 after co-culture with murine splenocytes from BCG vaccinated versus naïve C57BL/6 mice. BCG vaccination in our hands led to a reduction in bacterial burden after challenge withMycobacterium tuberculosis of approx. 0.7 log10 CFU in lung and approx. 1 log10 CFU in spleen. This effect was also seen when usingMycobacterium smegmatis as the target of growth inhibition. An increase in mycobacterial numbers was found when splenocytes from interferon gamma-deficient mice were used, compared to wild type controls, indicating that immune mechanisms may also be investigated using this assay. Conclusions We believe that theex vivo mycobacterial growth inhibition assay could be a useful tool to help assess vaccine efficacy in future, alongside other established methods. It could also be a valuable tool for determination of underlying immune mechanisms.